2019
DOI: 10.1177/1756287219839631
|View full text |Cite
|
Sign up to set email alerts
|

Real-time indocyanine green angiography with the SPY fluorescence imaging platform decreases benign ureteroenteric strictures in urinary diversions performed during radical cystectomy

Abstract: Background: Ischemia is thought to contribute to benign ureteroenteric stricture (UES) after radical cystectomy with urinary diversion (RCUD). Our institution adopted the use of ureteral perfusion assessment during all RCUDs using real-time indocyanine green angiography using the SPY fluorescence imaging platform (Stryker Corp., Kalamazoo, MI, USA). This guides the location of ureteral transection prior to ureteroenteric anastomosis. We sought to compare UES rates before and after adoption of SPY.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 26 publications
0
16
0
2
Order By: Relevance
“…reviewed outcomes of 94 patients who underwent RARC. 21 For the 47 patients who had the procedure carried out with ICG fluorescence, the rate of UES development was significantly lower after a median follow-up period of 12.0 months (0% vs 7.5%; P = 0.01). A study by Ahmadi et al reviewed 179 patients undergoing RARC-ICUD, in which 47 patients underwent surgery with the use of ICG.…”
Section: Discussionmentioning
confidence: 83%
“…reviewed outcomes of 94 patients who underwent RARC. 21 For the 47 patients who had the procedure carried out with ICG fluorescence, the rate of UES development was significantly lower after a median follow-up period of 12.0 months (0% vs 7.5%; P = 0.01). A study by Ahmadi et al reviewed 179 patients undergoing RARC-ICUD, in which 47 patients underwent surgery with the use of ICG.…”
Section: Discussionmentioning
confidence: 83%
“…Recent work by Shen et al has demonstrated potential for the use of intraoperative fluorescent angiography during open urinary diversion in reduction of ureteroenteric stricture rates. In a series of 47 patients, no ureteroenteric strictures were detected in the experimental group [ 20 ]. These studies show promise for widespread reduction in ureteroenteric stricture rates by assessing ureteral perfusion prior to making ureteroenteric anastomosis, as the technique will not be limited to robotic only approach.…”
Section: Discussionmentioning
confidence: 99%
“…ICG can also be used for perfusion assessment for liver segments, 33 ureters [34][35][36] (Table 4 and Figure 3) and during various flap reconstructive procedures.…”
Section: Other Uses Of Perfusion Assessmentmentioning
confidence: 99%